The Effect of Augmented Reality Cartoon Learning Media Integrated with Tri-sipaka Values on Student Awareness of the Three Great Sins in Education - Amaliah M., Arizka; Nengsi, Devi Wahyu; B.Hi.Muhammad, Ummu Salamah; Amaliyah, Nadifah; Hidayat, Wahyu; Patongai, Dian Dwi Putri Ulan Sari (PT ARRUS Intelektual Indonesia, 2024)
This study aims to determine the influence and effectiveness of the use of ARTOON: Augmented Reality Cartoon learning media integrated with Tri-sipaka values in increasing students' awareness of the three major sins in education, namely bullying, sexual violence, and intolerance. The research method uses a mixed method approach with convergent design. The population in this study was grade XI students of SMA Negeri 11 Pinrang and the sample used consisted of all grade XI students specializing in biology totaling 43 students. Sample withdrawal uses the Non-probability sampling technique with the purposive sampling method. Using a mixed method approach with convergent design, the study involved 43 students in grade XI of SMA Negeri 11 Pinrang. The data analysis technique uses descriptive analysis, inferential statistics with Paired Sample T-test, Miles and Huberman interactive analysis for qualitative data, and data interpretation. The results of this study show that there is an influence of the application of augmented reality cartoon learning media integrated with tri-sipaka values in increasing students' awareness of the three major sins in education. In addition, this learning media has also proven to be effective in increasing students' awareness of the three major sins in education. The results of this study can be a reference for schools in terms of integrating tri-sipaka values in learning.